Issues of Influence of National Values on Understanding of National Identity in Modernizing Uzbekistan - Kimsanbayeva Shakhnoza Bakridinovna, (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
In this article, the religious ideas, ceremonies, and holidays existing in ancient Central Asia are analyzed, and the values corresponding to the present time are separated and analyzed separately. Also, in the article, certain views formed in social life about religious heritage and understanding of national identity are comparatively studied. In the conditions of spiritual renewal of society, in a situation where the conceptual idea of "from national revival to national rise" is being implemented, the influence of the religious heritage of our ancestors on the understanding of national identity was analyzed using the principles and categories of social philosophy.